2022
DOI: 10.1371/journal.pone.0262800
|View full text |Cite
|
Sign up to set email alerts
|

Multi-parametric analysis of speech timing in inter-talker identical twin pairs and cross-pair comparisons: Some forensic implications

Abstract: The purpose of this study was to assess the speaker-discriminatory potential of a set of speech timing parameters while probing their suitability for forensic speaker comparison applications. The recordings comprised of spontaneous dialogues between twin pairs through mobile phones while being directly recorded with professional headset microphones. Speaker comparisons were performed with twins speakers engaged in a dialogue (i.e., intra-twin pairs) and among all subjects (i.e., cross-twin pairs). The particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 66 publications
1
3
0
Order By: Relevance
“…When comparing previous analyses with data from Brazilian Portuguese [4,5], a relatively similar pattern was also suggested, in which speech temporal parameters performed worse compared to melodic estimates, as revealed by the discrepancy in Cllr and EER values.…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…When comparing previous analyses with data from Brazilian Portuguese [4,5], a relatively similar pattern was also suggested, in which speech temporal parameters performed worse compared to melodic estimates, as revealed by the discrepancy in Cllr and EER values.…”
Section: Introductionsupporting
confidence: 58%
“…Overall, six acoustic-phonetic parameters were chosen for the comparison based on their relatively better discriminatory performance in relation to other parameters of the same category assessed in previous studies, cf. [4,5,7]. The Praat script "ProsodyDescriptorExtractor" [8] was used for the extractions:…”
Section: Acoustic-phonetic Parametersmentioning
confidence: 99%
“…It should also be acknowledged that, as previous studies suggest, cf. Heuvel ( 1996 ) and Cavalcanti et al ( 2022 ), an uneven level of speaker specificity appears to be present within the speech temporal domain itself. In Cavalcanti et al ( 2022 ), for instance, it was observed that macro speech timing parameters (e.g., speech and articulation rates) appeared to contain more speaker-specific information in relation to micro speech timing parameters (e.g., vowel and syllable duration).…”
Section: Discussionmentioning
confidence: 89%
“…Heuvel ( 1996 ) and Cavalcanti et al ( 2022 ), an uneven level of speaker specificity appears to be present within the speech temporal domain itself. In Cavalcanti et al ( 2022 ), for instance, it was observed that macro speech timing parameters (e.g., speech and articulation rates) appeared to contain more speaker-specific information in relation to micro speech timing parameters (e.g., vowel and syllable duration). According to the arguments presented in that paper, a low explanatory potential of the speaker identity regarding micro-temporal parameters may suggest those units as under a higher level of linguistic control.…”
Section: Discussionmentioning
confidence: 89%